Numerical simulation modeling of the irreversible electroporation treatment zone for focal therapy of prostate cancer, correlation with whole-mount pathology and T2-weighted MRI sequences. (June 2019) - Scheltema, Matthijs J.; O'Brien, Tim J.; van den Bos, Willemien; de Bruin, Daniel M.; Davalos, Rafael V.; van den Geld, Cees W.M.; Laguna, Maria P.; Neal, Robert E.; Varkarakis, Ioannis M.; Skolarikos, Andreas; Stricker, Phillip D.; de Reijke, Theo. M.; et al.
Background: At present, it is not possible to predict the ablation zone volume following irreversible electroporation (IRE) for prostate cancer (PCa). This study aimed to determine the necessary electrical field threshold to ablate human prostate tissue in vivo with IRE. Methods: In this prospective multicenter trial, patients with localized PCa were treated with IRE 4 weeks before their scheduled radical prostatectomy. In 13 patients, numerical models of the electrical field were generated and compared with the ablation zone volume on whole-mount pathology and T2-weighted magnetic resonance imaging (MRI) sequences. Volume-generating software was used to calculate the ablation zone volumes on histology and MRI. The electric field threshold to ablate prostate tissue was determined for each patient. Results: A total of 13 patients were included for histological and simulation analysis. The median electrical field threshold was 550 V/cm (interquartile range 383–750 V/cm) for the software-generated histology volumes. The median electrical field threshold was 500 V/cm (interquartile range 386–580 V/cm) when the ablation zone volumes were used from the follow-up MRI. Conclusions: The electrical field threshold to ablate human prostate tissue in vivo was determined using whole-mount pathology and MRI. These thresholds may be used to develop treatment planning or monitoring software for IRE prostate ablation; however, further optimization of simulation methods are required to decrease the variance that was observed between patients.